Análise crítica da operação radial dos sistemas de distribuição de energia elétrica - Ritter, Donizete [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The distribution systems typically operate with a radial topology, thus, traditionally in reconfiguration an optimal radial topology is explored in which it allows the system to operate with minimal losses. All reconfiguration models of these systems consider the radiality in their formulation, either in implicit form (heuristics and metaheuristics) or explicit form (exact optimization). However, the optimum radial topology is inferior to that of non-radial in terms of losses. This paper presents, in a first phase, a literature review on the radiality constraints, considerations about this condition in a distribution system, the modeling of the “traditional” reconfiguration problem using exact optimization, and finally a proposal to relax the radiality constraints of this mathematical model, thereby allowing the new model to find the optimal topology in terms of losses. Tests presented show that it may be appropriate to rethink the logic of the traditional operation and search for nearby topologies of radial topologies to reduce operating losses. We think that the new logic becomes relevant when considering the current context in which the concept of intelligent networks (smart grids) is the operating philosophy in modern distribution systems. To prove the performance of the proposed method in this paper, we present the results for systems of 14, 33, 84, 119 and 136 buses. A methodology is presented to solve the problem of distribution system reconfiguration with relaxed radiality considering simultaneously two objectives: energy losses and short-circuit current. The proposal developed is the main contribution of this paper and has been tested on systems of 33 and 136 buses

Os sistemas de distribuição normalmente operam com uma topologia radial, assim, tradicionalmente, a reconfiguração procura a topologia radial ótima que permite que o sistema opere com perdas mínimas. Todos os modelos de reconfiguração desses sistemas consideram a radialidade em sua formulação, seja de forma implícita (heurísticas e meta-heurísticas), ou de forma explícita (otimização exata). No entanto, a topologia radial ótima é inferior a outras topologias, não-radiais, em relação às perdas. Assim, este trabalho apresenta, em um primeiro momento, uma revisão da literatura sobre as restrições de radialidade, considerações sobre esta condição em um sistema de distribuição, a modelagem “tradicional” do problema de reconfiguração usando otimização exata e, finalmente, uma proposta para relaxar as restrições de radialidade nesse modelo matemático, permitindo assim que o novo modelo encontre a topologia realmente ótima em termos de perdas. Testes apresentados mostram que pode ser oportuno repensar sobre essa lógica de operação tradicional e procurar por topologias próximas das topologias radiais para diminuir as perdas de operação. Consideramos que a nova lógica se torna relevante quando consideramos o contexto atual em que o conceito de redes inteligentes (smart grids) representa a filosofia de operação nos modernos sistemas de distribuição. Para comprovar a premissa sustentada neste trabalho, apresentamos os resultados para sistemas de 14, 33, 84, 119 e 136 barras. É apresentada uma metodologia para resolver o problema de reconfiguração de sistemas de distribuição com a radialidade relaxada considerando, simultaneamente, dois objetivos: perdas de energia elétrica e corrente de curto-circuito. A proposta desenvolvida é a principal contribuição deste trabalho e foi testada nos sistemas de 33 e de 136 barras
Keywords: Energia elétrica - Distribuição; Sistemas de energia eletrica; Programação (Matemática); Electric power systems